Variations in position of mandibular foramen with age and its efficacy in sex estimation - Mohite, Deepali P; Mohite, Prakash M; Hande, Alka H; Palve , Devendra (Journal of Indian Academy of Forensic Medicine, 2021)
Forensic Odontology is a rapidly evolving branch of dentistry which deals with the identification of an individual. In instances of deceased individual, establishing identity may still pose difficulties depending upon the time that has elapsed since death. The oral structures are very well preserved for a long time since death as they are protected from the external environment by the facial soft tissues and bone. So these structures can reliably be used for establishing identity of the deceased. The mandibular foramen has been used in this study for the reason that it is amongst the core structures of Oral Cavity and remains unaffected after death. The mandibular foramen has been used for age estimation with reliable degree of accuracy using radiographs which is a non-invasive and easily reproducible technique hence we decided to assess its importance in establishing gender. Digital Orthopantomograph (OPG) were used for the study as they are taken for all dental procedures and can be preserved as records and may facilitate comparison of ante-mortem and post-mortem records. Various dimensions from the mandibular foramen were recorded and we found statistically significant correlation of Anteroposterior and Posteroanterior dimensions in position of mandibular foramen to gender.